ISOLASI DAN IDENTIFIKASI SENYAWA ANTIBAKTERI MINYAK ATSIRI DAUN KEMBANG BULAN {Tithonia diversifolia (Hemsley) A. Gray} - Hartati Soetjipto; Lusiawati Dewi; Sentot Adi Prayitno (BERITA BIOLOGI, 2008)
Isolation and identification of chemical compounds and antibacterial compounds of the essential oil of Kembang bulan or Japanese sunflower {Tithonia diversifolia (Hemsley) A. Gray} leaves showed that the essential oil contain 29 components. The main components were caryophyllene (27.76%), nerolidol (21.81%),caryophyllene oxide (7.06%), copaene (6.41%) and bicylogermacrene (4.90%). The oil was screened for their antibacterial activity through bioautography method. Two antibacterial spots which had Rf 0.49 and Rf 0.61were obtained. The spot with Rf 0.49 was a mixture of 21 compounds with main compounds were heneicosane, nonacosane and tetratetracontane, while the spot with Rf 0.61 consisted of 22 compounds, which the main compound was nerolidol.